Avaliação das transferências voluntárias da União em programas de infraestrutura da reforma agrária brasileira - Moreira, Daniel Marques (2019)
The planning and execution of public policies in Brazil, in the context of fiscal federalism, makes use of intergovernmental transfers, which are responsible for much of the income of the federation’s entities. Some of these transfers are mandatory, with predetermined transfer quotas, some are discretionary, as is the case with voluntary transfers. Most scientific publications on voluntary transfers analyze events prior to the release of resources. However, in addition to the motivations that exist in the formalization of transfers or the budgetary targets established for decentralization, it is necessary to know the efficiency and effectiveness parameters of this management model. This study’s goal is to evaluate the implementation performance of voluntary transfers aimed at the execution of infrastructure programs in land reform areas. The programs were intended for the execution of road infrastructure, sanitation and energy works in rural areas. The study methodology involved an applied and documentary research, with a descriptive quantitative approach, analyzing 150 programs that integrate the Pluriannual Plan (PPA) 2012-2015. The information was taken from the Federal Government Covenants Portal. By analyzing 321 formalized transfers through covenants, the research built performance indices to evaluate implementation, execution and temporality, as well as identifying and measuring the causes of failure in the implementation of transfers. The results show that the voluntary transfers presented little implementation effectiveness. The reasons for not completing the works and accounts’ disapproval, the reasons for the annulment of covenants and the difficulties of execution from the perspective of the public agency that received the funds were highlighted. By the 2018 reading, three years after the 2012-2015 PPA closed, more resources had been set aside for unsuccessful transfers than for successfully completed transfers. In the evaluation of temporality, it was evidenced that the effectiveness of the agreements was on average three times longer than the deadline defined in the act of celebration and five times higher than the work schedule defined in the engineering project. The average time required to complete the works was four times longer than the engineering project schedule. The identification of behavioral patterns of voluntary transfers implementation ends up exposing management weaknesses and may help researchers and policymakers to understand successes and failures for process improvements. Also, the results are particularly relevant for regulators, as a better understanding of performance can lead to the refinement of program rules and standards, often not associated with voluntary transfers themselves, but rather their management.